Analisis Efisiensi Panel Surya Menggunakan Reflektor Dan Sistem Pendingin Berbasis Mikrokontroler - Muhamad Jafri (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
The addition of reflectors to solar panels to redirect solar radiation onto the panel surface can lead to increased surface temperatures. Excessive temperature rise significantly impacts the power output. The implementation of a microcontroller-based cooling system can optimize the temperature on the solar panel surface. The research employs an experimental method on four test media, namely solar panels with reflectors at angles of 45° and 60°, with the addition of a microcontroller-based cooling system, solar panels without reflectors with a cooling system, and solar panels without reflectors or cooling system (as the control). The aim of this study is to determine the efficiency of solar panels using reflectors and a microcontroller-based cooling system. The test results indicate that the intensity of light and temperature also affect the generated power. The microcontroller-based cooling system applied to the solar panel maximizes the power output and efficiency. The solar panel using a 60° reflector with cooling produces a power output of 14.10 Watt with an efficiency of 15.9%, while the solar panel using a 45° reflector produces a power output of 14.07 Watt with an efficiency of 15.4%. The solar panel without a reflector but with a cooling system produces a power output of 13.31 Watt with an efficiency of 14.4%, which is higher than the solar panel without a reflector or cooling system, which only produces a power output of 11.264 Watt with an efficiency of 12.1%.